Screening for mobile colistin resistance gene-9 (mcr-9) in multidrug resistant uropathogenic Escherichia coli isolated from patients with urinary tract infections - Divya Lakshmanan; K. Vanathy; Catherine Thamayandhi; Sreejith Sreekumaran; E. K. Radhakrishnan; S. Srirangaraj (BMC Research Notes)
Abstract Objective Colistin and Polymyxin B form the reserve group of antibiotics. Resistance to colistin has been increasing across the world including India, posing treatment challenges to clinicians. Use of colistin as a feed supplement in livestock and aquaculture sectors have contributed to the spread of resistance, underlining the need for surveillance among clinical isolates in hospitals. Recently, presence of 10 variants of plasmid-associated mobile colistin resistance (mcr) genes have contributed to colistin resistance in the Gram-negative Enterobacterales. Of these, the mcr-9 is unique in terms of its inducible character in presence of sub-lethal concentrations of colistin, making it clinically relevant. A recent report of mcr-9 from an environmental isolate from Pondicherry prompted us to probe whether the gene cross-over has occurred to our clinical uropathogenic isolates. In this study, we screened for colistin susceptibility and presence of mcr-9 gene among 88 multidrug resistant clinical isolates of uropathogenic E. coli obtained from urine samples of patients with urinary tract infections attending our tertiary care hospital. Results We found that none of the isolates that we screened were colistin or polymyxin B resistant and mcr-9 gene was absent, indicating that there was no cross-over of mcr-9 resistance from the environment to clinical UPEC strains.